Hybrid vigour and variability for key growth characters and yield in cashew (Anacardium occidentale L.) - Eradasappa, E.; Adiga, J. D.; Mohana, G.S. (Journal of Plantation Crops, 2020)
Hybrid vigour and assessment of genetic variability for important growth characters and yield traits in cashew were studied in eight cashew hybrids.The analysis of variance for the phenotypic data for 12 characters revealed significant variation among the genotypes except for tree spread, flowering laterals per m2, non-flowering laterals per m2 and sex ratio.The highest nut weight was observed in H-125 (12.07 g) whereas the lowest was in H-2452 (5.08 g).The maximum nut yield was noticed in hybrid H-126 with 5.96 kg tree-1 while NRCC Selection-2 recorded lowest with 0.53 kg tree-1. The standard heterosis over two checks, bold nut check (NRCC Sel-2) and high yielding check (Bhaskara) and variability parameters such as genotypic coefficient of variation, phenotypic coefficient of variation, broad-sense heritability and genetic advance were estimated. For nut weight, standard heterosis over bold nut check varied from -34.54 to 55.54 per cent and six out of eight hybrids viz., H-43, H-66, H-68, H-125, H-126 and H-2473 showed significant and positive standard heterosis. Standard heterosis over the high yielding check, varied from -38.93 to 300 per cent and it was significant and positive in two hybrids viz., H-126 and H-125 with 300 per cent and 214.09 per cent, respectively.The hybrid vigour was not significant for trunk girth, tree height, tree spread, number of flowering laterals per m2 and sex ratio. Notably, five hybrids presented more than 20 per cent standard heterosis for nut weight over bold nut check which may serve as a useful source of breeding material. Two hybrids viz., H-125 and H-126 showed good hybrid vigour for nut weight and yield over two checks and thus have been inducted into multi-location trials and also under consideration for release.